Preparation and Characterization of Freestanding Hierarchical Porous TiO2 Monolith Modified with Graphene Oxide - Wan, Lei; Long, Mingce; Zhou, Dongying; Zhang, Liying; Cai, Weimin (Nano-Micro Letters, 2012)
Catalyst recovery is one of the most important aspects that restrict the application of TiO2 photocatalyst. In order to reduce restrictions and improve the photocatalytic efficiency, a hierarchical porous TiO2 monolith (PTM) with well-defined macroporous and homogeneous mesoporous structure was prepared by using a sol-gel phase separation method. P123 was used as the mesoporous template and graphene oxide was applied to increase the activity and integrity of the monolithic TiO2. According to scanning electron microscopy and the Barrett-Joyner-Halenda measurements, PTM3 is mainly composed of 10 nm anatase crystallines with 3.6 nm mesopores and 2–8 μm macropores. Further characterization suggests carbon and nitrogen have been maintained in the PTM during calcinations so as to induce the visible light activity. The PTM with 0.07 wt% graphene oxide dosage shows high efficiency for methyl orange (MO) decolorization under both full spectrum and visible light irradiation (λ>400 nm). Besides, the monolith remains intact and has good photocatalytic stability after four cyclic experiments.